Immobilization and stabilization of volcanic ash in soil aggregates in semiarid meadows of Northern Patagonia - Enriquez, Andrea Soledad (2021)
Although volcanism may be perceived by the society as a phenomenon with mostly negative consequences, this is not always the case especially for natural systems. There is a limited knowledge on how the deposited pristine ash becomes immobilized and stabilized in the soil after the volcanic event. Here, we studied processes of soil aggregates formation in the buried ash layer in an early stage of the succession as well as the influence of the biological legacy (previous land management history) on these processes after the 2011 volcanic event of the Puyehue–Cord´on Caulle Volcanic Complex. 5.5 years after the eruption we collected soil cores to a 10 cm depth in wet and mesic meadows with good and poor grassland conditions induced by light and heavy grazing intensity, respectively, in the East semiarid region of North Patagonia, Argentina. The ash layer was observed down to 5 cm from the soil surface, clearly differentiating a newly developed soil layer formed after the volcanic event. Accordingly, the top 5 cm were examined for the distribution of different size fractions of water-stable soil aggregates and their associated organic carbon (C) and total nitrogen (N) contents. We detected signs of physical and physicochemical changes in respect to the pristine ash collected at these sites in 2011. Soil neoformation processes were detected through the presence of large (4%) and small (21%) macroaggregates, although microaggregates (~45%) and silt + clay fractions (~29%) dominated the soil mass (ash-soil matrix: 0–5 cm depth). C and N contents decreased in a sequence: large macroaggregates ≥ small macroaggregates > microaggregates ≥ silt + clay, highlighting the importance of soil organic matter in the formation of larger-size aggregates and their quality (C and N contents). Biological legacy influenced soil aggregate formation and their quality, as reflected by a higher mass of small macroaggregates and a lower mass of microaggregates (only in mesic meadows) and by higher C and N contents under good grassland conditions. The seasonal hydrological conditions of meadow soils (i.e., soil water content, wetting and drying cycles) via effects on biological and physical processes likely resulted in a reduced aggregation in wet meadows. We noticed an incipient but present soil aggregation processes in these semiarid wetlands translated in the immobilization and stabilization of the buried ashes in the soil. The total C content in the new 0–5 cm soil layer increased at a rate of 1.0 Mg C ha 1 yr 1, on average. This indicates a functional recovery of the ecosystem along with a substantial CO2 mitigation potential in the ashes stabilized with soil organic matter, which might partially counterbalance CO2 emitted during the eruption.